EFEKTIFITAS PENGGUNAAN MODUL KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN GURU PENDIDIKAN JASMANI (PENJAS) SEKOLAH DASAR - Dyah Umiyarni Purnamasari; Nur Ulfah; Kusnandar Kusnandar (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2014)
ABSTRACT Measurement of nutritional status and physical fitness of school children in the District of South Purwokerto not be interpreted as the complete data and performed routinely. This study aims to increase knowledge of physical education teachers through the provision of health module. The research method using a Quasi Experiment with design One Group Pre-Test and Post-Test. Test data analysis using Paired T-Test. The results showed differences in the results of the p-value = 0.000 <α: 0.05, thus indicating no significant differences in health knowledge through the media module to change the average score of knowledge that is 22.05. Suggestion to apply their knowledge for the measurement of nutritional status and physical fitness routine in the students so that the data obtained can be used to plan health interventions in school children. Key words : modul, nutritional status, physical fitness Kesmasindo, Volume 6, (3) Januari 2014, Hal. 176-182